Practices and Beliefs of Yemeni Pediatricians Regarding Neonatal Hyperbilirubinemia - Elnemr, Muna A. M.; Ibraheem, Doa'a A. (University of Science and Technology, Sana'a, 2011)
Neonatal hyperbilirubinemia is a widespread and significant clinical condition amongst neonates worldwide Methods: A specially designed questionnaire was distributed to a random sample of 200 pediatricians working in the main childhood hospitals in Sana'a. Results: The pediatricians involved in the study stated high use (61.8%) of the cephalo-caudal progression as a method to evaluate jaundice in the newborn. Less proportion of pediatricians tested total serum bilirubin levels in jaundiced neonates ahead of their discharge from the hospital as compared to jaundiced neonates examined at the post-discharge visit (73.9% vs. 83.4%). The majority of pediatricians did not believe neonatal jaundice noted after discharge and gestational ages 37-38 weeks as being risk factor for the development of acute bilirubin encephalopathy. A considerable number of our pediatricians initiated phototherapy as well as exchange transfusion at lower levels of serum bilirubin than the recommended by the AAP guidelines at age of 24-48 hr, (66.7% and 57.6% respectively). Conclusion: although Yemeni pediatricians in the study were liable to start up phototherapy and exchange blood transfusion at points lesser than those recommended, the study revealed an overall consistency of their practice with hyperbilirubinemia treatment guidelines of the American Academy of Pediatrics, 2004.